Cost-effectiveness analysis of population-based BRCA1/2 testing, family-history-based BRCA1/2 testing, and symptom-based screening for breast and ovarian cancer in China - Zhao, Feilong; Wang, Shu; Lu, Jianfei; Feng, Xiangying; Ran, Liwei; Yang, Jianjun (Frontiers in Public Health, 2025)
BackgroundThe women’s cancer screening program has been operational for several years in China, primarily utilizing palpation and ultrasound. Given the proven impact of BRCA1/2 mutations on the incidence of breast and ovarian cancer, the cost-effectiveness of incorporating BRCA1/2 mutation testing into these programs, either for the entire population or through enrichment based on family history of breast and ovarian cancer, remains poorly researched.MethodsWe constructed a decision tree model to compare the cost-effectiveness of three strategies: symptom-based screening only (Symptom-only strategy), population-based BRCA1/2 testing (population-based strategy), and family-history-based BRCA1/2 testing (FH-based strategy). One-way and probability sensitivity analyses enabled model uncertainty evaluation. Outcomes included early and advanced stages of ovarian and breast cancer. Cost, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs) were calculated. The target population was women at 40–60 years, the time horizon was until age 70, and the perspective was payer-based.ResultsThe FH-based strategy was found to be cost-effective compared to the Symptom-only strategy (ICER: ¥185,710/QALY, gaining 0.26 days’ life expectancy). Its cost-effectiveness was significantly influenced by the risks of ovarian and breast cancer among BRCA1/2 carriers, the prevalence of BRCA1/2 mutations in the general Chinese population, the prevalence of family history of breast and ovarian cancer among Chinese women, and the prevalence of BRCA1/2 mutations in the FH-positive population. Integrating these variable distributions, the FH-based strategy showed a 76.96% probability of cost-effectiveness. The Population-based strategy was not cost-effective, whether compared to the Symptom-only strategy (ICER: ¥504,476/QALY, gaining 2.66 days’ life expectancy) or to the FH-based strategy (ICER: ¥539,476/QALY, gaining 2.41 days’ life expectancy). The prevalence of BRCA1/2 mutations in the general Chinese population was identified as the primary variable affecting its cost-effectiveness. Integrating these variable distributions, the Population-based strategy had a probability of cost-effectiveness of only 0.8%.ConclusionIncorporating family-history-based BRCA1/2 testing into breast and ovarian cancer screening programs is cost-effective in China and warrants promotion.